1995
DOI: 10.1111/j.1469-8137.1995.tb04311.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of nitrogen in vacuolar bodies of Cenococcum geophilum Fr. mycorrhizas as detected by electron energy loss spectroscopy

Abstract: SUMMARYNitrogen fertilization of potted Pinus sylvestris L. seedlings growing in forest humus was carried out using two different concentrations of ainmonium sulphate and ammonium chloride, corresponding to 50 and 100 kg N ha~Ĉ enococcum geophilum Fr. mycorrhizas were collected from the root systems of the seedlings and investigated by light and transmission electron microscopy. The number of vacuolar osmophilic bodies in the mantle byphae significantly increased after fertilization witb both atnmonium salts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Carbon was highly detected in these bodies, since it is the main element in the organic compounds of the storage structures. In some of vacuoles and BLO P was also found, however in those bodies where P was not detected, it is not possible to consider them devoid of it, because the detection limit of EELS in biological material is not yet clarified (Kottke et al 1995). Some N and P loss might occur during the preparation of the material (Young et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbon was highly detected in these bodies, since it is the main element in the organic compounds of the storage structures. In some of vacuoles and BLO P was also found, however in those bodies where P was not detected, it is not possible to consider them devoid of it, because the detection limit of EELS in biological material is not yet clarified (Kottke et al 1995). Some N and P loss might occur during the preparation of the material (Young et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Electron energy loss spectroscopy (EELS) -The amounts of N, C and P in the spores were measured on sections 40-50nm thick, without further treatment, by using the Electron Energy Loss Spectroscopy (EELS), connected to the TEM, according to the procedures described by Kottke (1991) and Kottke et al (1995). The system was set as follows: Spectra were acquired at a magnification of 50,000.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even at the lowest N application rate, osmiophilic vacuolar bodies were present in the fungal tissue, especially in the mantle. Recently, Kottke et al (1995) demonstrated the sequestration of N and P in these vacuolar bodies in Pinus sylvestris\Cenococcum geophilum mycorrhizas. Fertilization with both NH % Cl or (NH % ) # SO % with 50 or 100 kg N ha −" during the 9-wk growth period increased the number of osmiophilic vacuolar bodies.…”
Section:  mentioning
confidence: 99%